The complete chloroplast genome sequence of Oryza sativa aus-type variety Nagina-22 (Poaceae). Issue 2 (20th December 2017) - Yu, Yeisoo; Lee, Hyun-Oh; Chin, Joong Hyoun; Park, Han Yong; Yoo, Soo-Cheul
Abstract: Rice ( Oryza sativa ) is the predominant staple food crop belonging to the Poaceae family. In this study, complete chloroplast genome sequence of O. sativa aus -type variety Nagina-22 was characterized through de novo assembly. The genome is a circular DNA molecule of 134, 503 bp and has typical quadripartite structures including large single copy region (80, 548 bp), small single copy region (12, 347 bp), and a pair of inverted repeats (20, 804 bp). A total of 120 genes were predicted in the genome, including 77 protein-coding genes, 8 open reading frame genes, 31 tRNA genes, and 4 rRNA genes. Phylogenetic analysis confirmed a close taxonomical relationship with O. sativa ssp. Indica species.